The effect of external suction at the dust outlet of a cyclone - Dewika, M*; Rashid, M; Hasyimah, N (Universiti Teknologi Malaysia Press, 2017)
Cyclone is one of the most commonly used particulate dust collectors in industries. It employs centrifugal force generated by a spinning gas stream to separate the particulate matter from the carrier gas. However, cyclone is efficient to collect coarse rather than fine particulate size fraction. In this regard, a study was carried out to determine the effect of creating more negative pressure at the storage hopper of a 100 mm diameter laboratory scale cyclone. The negative pressure was created by drawing out a small portion of the gas stream by means of an air pump attached to the storage hopper. Results showed that there was exponentially related between the pressure drop (ΔP) and the amount of gas stream drawn at the storage hopper, but with an increment of 2.6% with suction compared to without. Interestingly, it was observed that more of the fine particulate matter was drawn from the gas stream as the suction flow rate increases. This is due to the suction velocity which exceeds the terminal falling velocities of the fine particles size range. There was a reduction by weight in the fine particle emitted from the cyclone ranging between 14% to 52% by introduction of the suction. The finding serves as a basis for future work in reducing fine particulates from a cyclone separator.